2020
DOI: 10.3390/molecules25061276
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds, Antioxidant Activities, and Inhibitory Effects on Digestive Enzymes of Different Cultivars of Okra (Abelmoschus esculentus)

Abstract: In this study, the phenolic profiles and bioactivities of five representative cultivars of okra collected in China were investigated. Noticeable variations of phenolic compounds and their bioactivities were observed among these different cultivars of okra. The contents of total flavonoids (TFC) in “Shuiguo”, “Kalong 8”, “Kalong 3”, “Wufu”, and “Royal red” ranged from 1.75 to 3.39 mg RE/g DW, of which “Shuiguo” showed the highest TFC. Moreover, five individual phenolic compounds were found in okra by high perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 28 publications
1
32
2
Order By: Relevance
“…The results are in agreement with D'Urso et al [35] and one more flavonoid (Q7G) was identified in our research. In addition, the separation and identification of flavonoids in okra in this study is much further based on previous studies [14,36,37]. Among the six components, Q3G, ISO, Q3S and Q3M were the main individual flavonoids, accounting for more than 96% of the total flavonoid.…”
Section: Discussionmentioning
confidence: 67%
“…The results are in agreement with D'Urso et al [35] and one more flavonoid (Q7G) was identified in our research. In addition, the separation and identification of flavonoids in okra in this study is much further based on previous studies [14,36,37]. Among the six components, Q3G, ISO, Q3S and Q3M were the main individual flavonoids, accounting for more than 96% of the total flavonoid.…”
Section: Discussionmentioning
confidence: 67%
“…The interaction of phenolic compounds with cholesterol esterase is due to the presence of potent cholesterol esterase inhibitory sites, especially the interaction with the catalytic triad and oxyanion hole residues [ 49 ]. Our previous study also reported that hydroethanolic extract and ethyl acetate fraction have antioxidant properties [ 28 , 29 ], and it is shown that a positive correlation exists between phenolic compounds, antioxidant activity of plant extracts, and digestive enzyme inhibitory activity [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pancreatic cholesterol esterase inhibition activity of leaves extracts and fractions of P. glandulosus were performed spectrophotometrically based on the method of Adisakwattana et al [36]. The extract/fraction (50 μL) at different concentrations (12,5,25,50, 100, 200 μg/mL) was incubated with mixtures containing 50 μL of taurocholic acid (5.16 mM), 50 μL of p-nitrophenyl butyrate substrate (0.2 mM), and 90 μL of sodium phosphate buffer (100 mM, pH 7.0). The reaction was initiated by adding 50 μl of porcine pancreatic cholesterol esterase (1 μg/mL).…”
Section: Cholesterol Esterase Inhibition Assaymentioning
confidence: 99%
“…Polysaccharides and phenolic compounds are the main bioactive components of okra. In the fruit and its extracts, one can find the phenolic compounds catechin, isoquercitrin, protocatechuic acid, quercetin, quercetin-3-O-gentiobioside, and rutin [ 63 ]. In okra mucilage, Nampuak and Tongkhao [ 64 ] observed the presence of catechin, epigallocatechin gallate, and quercetin compounds.…”
Section: Composition and Physicochemical Characteristics Of Okra Mucilagementioning
confidence: 99%